Development of a national audit tool for juvenile idiopathic arthritis: a BSPAR project funded by the Health Care Quality Improvement Partnership. (23rd October 2017) - McErlane, Flora; Foster, Helen E; Armitt, Gillian; Bailey, Kathryn; Cobb, Joanna; Davidson, Joyce E; Douglas, Sharon; Fell, Andrew; Friswell, Mark; Pilkington, Clarissa; Strike, Helen; Smith, Nicola; et al.
Abstract: Objective: Timely access to holistic multidisciplinary care is the core principle underpinning management of juvenile idiopathic arthritis (JIA). Data collected in national clinical audit programmes fundamentally aim to improve health outcomes of disease, ensuring clinical care is equitable, safe and patient-centred. The aim of this study was to develop a tool for national audit of JIA in the UK. Methods: A staged and consultative methodology was used across a broad group of relevant stakeholders to develop a national audit tool, with reference to pre-existing standards of care for JIA. The tool comprises key service delivery quality measures assessed against two aspects of impact, namely disease-related outcome measures and patient/carer reported outcome and experience measures. Results: Eleven service-related quality measures were identified, including those that map to current standards for commissioning of JIA clinical services in the UK. The three-variable Juvenile Arthritis Disease Activity Score and presence/absence of sacro-iliitis in patients with enthesitis-related arthritis were identified as the primary disease-related outcome measures, with presence/absence of uveitis a secondary outcome. Novel patient/carer reported outcomes and patient/carer reported experience measures were developed and face validity confirmed by relevant patient/carer groups. Conclusion: A tool for national audit of JIA has been developed with the aim of benchmarking current clinical practice and setting future standards and targets for improvement. Staged implementation of this national audit tool should facilitate investigation of variability in levels of care and drive quality improvement. This will require engagement from patients and carers, clinical teams and commissioners of JIA services.